Pendidikan Inklusif Dan Pemenuhan Hak Anak Berkebutuhan Khusus Di Indonesia: Tinjauan Literatur Kritis - Nusaibah, Shifa; Nanariain, Diana Michelle Darlene; Istiqamah , Dyah (Publikasi Indonesia, 2025)
Education is the human right of every child, including children with special needs, which must be fulfilled without discrimination. In Indonesia, although there are various regulations that support the implementation of inclusive education, its implementation in the field still faces various challenges that have an impact on the fulfillment of the basic rights of children with disabilities. This study aims to critically analyze the implementation of inclusive education in Indonesia, assess the extent to which the rights of children with disabilities have been fulfilled, and formulate policy recommendations that are more favorable. This research uses a critical literature review method with a qualitative approach, based on eight scientific articles published between 2021-2025. The results show that although Indonesia has a legal framework that supports the implementation of inclusive education, the implementation in the field still faces various obstacles, both in terms of human resource readiness, infrastructure and public understanding. The conclusion of this study emphasizes the importance of strengthening the basic components as well as the collaboration of various parties and adjusted to the principle of non-discrimination. Further research is recommended to explore good practices in inclusive schools as a basis for developing policy and training models that are more applicable and contextualized